Pendidikan Islam Era Dinasti Turki Usmani - Sejati, Abdiana; Mawardi, Kholid (Transformasi Manageria Journal of Islamic Education Management, 2024)
The education system played an important role in the development and expansion of the Ottoman Empire. To provide the country with well-trained and meritorious leaders, special institutions, such as court schools, were established. During its heyday, the Ottoman Empire reached new heights of intellectual achievement. During the success of civilization, this system gave birth to scholars who thought highly and had high knowledge. Empire growth stagnated and became resistant to change and innovation, with lasting consequences for society. Based on this, this article discusses, describes, and analyzes Islamic education in the Ottoman Empire. The object of this research is a literature search with a qualitative descriptive method. Qualitative descriptive research is research that describes existing data. This study uses historical methods. Education during the Ottoman Empire was driven by advanced educational institutions during the Ottoman empire, namely madrasas. In this case it is not just the number of buildings, but the quality of education offered by producing scholars who are experts in their fields. Keywords: Islamic Civilization, Islamic Education, Ottoman Turks.